PRODUKTIVITAS, RENDEMEN DAN KONTRIBUSI KERAJINAN BAMBU (Bambusa sp) TERHADAP PENDAPATAN DI DESA TAMBAK BARU KECAMATAN MARTAPURA TIMUR KABUPATEN BANJAR - Gusti Ahmad Erfani; Zainal Abidin; violet violet (Jurnal Sylva Scienteae, 2020)
Non-timber forest products are generally used for their own needs, building materials and craft materials. Non-wood species that are widely available in the field are bamboo. Bamboo is widely used by the community for various kinds of crafts through various processing processes. The results showed the average time needed by the craftsmen to produce one Bungkalang that is 3.01 hours and make one fruit that is 4.36 hours. Factor affecting productivity include length of time work, individual ability, age of craftsman, and level education. The yield of Bungkalang ranged from 63.86%-70.68% with the overall average yield of Bungkalang handicrafts 66.6% and tampirai ranging from 64.43%-72.12% with the average yield of Tampirai handicrafts 67.76%. The average raw material cost of bungkalang craftsmen is Rp.5,707,500/year. The average total income of artisans is Rp12,230,400/year, with an average net income of Rp6,522,900 a year.The total income of the attached craftsmen is Rp.17,348,181.82 / year, with an average raw material cost of Rp7,517,500/year. The average net income of the craftsman of the tampirai is Rp9,830,600/year. and total income of Rp13,980,000 / year. The income from the bungkalanghandicraft is Rp71.752.000/year with average income of Rp6.522.900/tahun, and average contribution 41,85%. The income from the tempirai handicraft is Rp108.137.000/year with average income of Rp9.830.600/year, and average contribution 49,08%. The total income of all craftsmen is Rp224,537,000/year, with an average of Rp20,412,400/year.